1972
DOI: 10.1084/jem.136.3.426
|View full text |Cite
|
Sign up to set email alerts
|

Hapten-Specific Tolerance

Abstract: The treatment of guinea pigs with 2,4-dinitrophenyl (DNP) t derivatives of the copolymer of D-glutamic acid and D-lysine (D-GL) induces a state of specific immunologic tolerance in the recipient (1). The type of tolerance induced is unusual in that it is DNP specific. That is, challenge of such guinea pigs with a DNP conjugate of ovalbumin (DNP-OVA) elicits anti-DNP responses markedly smaller than those of animals which have not been pretreated with DNP-B-GL. The degree of depression in responsiveness is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1973
1973
1977
1977

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…The high avidity of the residual PFC and serum antibody in animals rendered tolerant by a low dose of soluble antigen is very different from previous studies in which tolerance has been associated with decreased antibody affinity (13)(14)(15)(16)(17)(18) . This difference in results suggested that the tolerance being studied in the present model is due to a distinctly different mechanism.…”
Section: Methodscontrasting
confidence: 52%
See 1 more Smart Citation
“…The high avidity of the residual PFC and serum antibody in animals rendered tolerant by a low dose of soluble antigen is very different from previous studies in which tolerance has been associated with decreased antibody affinity (13)(14)(15)(16)(17)(18) . This difference in results suggested that the tolerance being studied in the present model is due to a distinctly different mechanism.…”
Section: Methodscontrasting
confidence: 52%
“…Consequently, B-cell tolerance has been found to be associated with a marked depression in antibody affinity (13,(15)(16)(17)(18) . The tolerant state described in the current work is thus distinctive in that it is associated with an increase in antibody affinity .…”
Section: Discussionmentioning
confidence: 99%
“…The most effective methods employed have the common feature of treating animals with haptenic determinants on molecules or substances that fail to stimulate T cells, or do so very poorly. Thus, such tolerance has been induced by administration of (a) hapten on nonimmunogenic moieties such as the synthetic copolymers of D-glutamic acid and n-lysine (D-GL), 1 or ~GL in PLL nonresponder guinea pigs (5,6) or inbred mice (7,9), (b)haptenic derivatives of autologousproteins (10)(11)(12)(13)(14), autologous or syngeneic red cells (15), or (c) polysaccharides such as type III pneumococcal polysaccharide (16,17). We suggested earlier that a possible explanation for the ease of tolerance induction with the hapten conjugates of nonimmunogenic copolymers such as D-GL and also for other non-or weakly immunogenic substances may be the lack of the simultaneous occurrence of immunization and tolerance induction when these substances are administered in appropriate conditions (1, 5).…”
Section: (From the Department Of Pathology Harvard Medical School Bmentioning
confidence: 99%
“…It also offers a clue to the understanding of more sophisticated roles of T cells in the regulation of antibody response, namely, the selective pressure of T cells on B-cell response with respect to the 'shift' in the class and affinity of produced antibody in the time course of antibody response. Furthermore, the preferential suppression of high affinity antibody formation caused by suppressor T cells is clearly analogous to the feature in the immunological tolerance produced by high doses of antigen (27)(28)(29). In view of the observation made by Gershon and Kondo (30) on the infectiousness of immunological tolerance by T cells, the attribute of suppressor T cells to the induction of immunological tolerance should await further analysis.…”
Section: Suppression Of Relative Avidity Of Pfc For Hapten By Carriermentioning
confidence: 99%